Analisis Konflik antara Pemerintah Provinsi Jawa Timur dan Pemerintah Kota Surabaya dalam Penggunaan Mobil PCR di Masa Pandemi Covid-19 - Ahmed, Indra Nur Ramadhan (Journal Politique, 2023)
The purpose of this thesis is to find out the causes behind the conflict between the East Java Provincial Government and the Surabaya City Government in the use of PCR cars, to determine the form of conflict that occurred between the East Java Provincial Government and the Surabaya City Government in the use of PCR cars, and also to know the conflict resolution taken by the East Java Provincial Government with the Surabaya City Government. This study uses a qualitative research method with a descriptive qualitative approach. The results of this study explain about 1.) The background of the cause of the conflict is the difference in the interests of the Surabaya City Government which wants its territory to immediately accelerate the detection of Covid-19 for the citizens of Surabaya City, while the interests of the East Java Provincial Government are to balance the needs in other areas that need assistance, and there was a miscoordination on the scheduling of this PCR car assistance. 2.) The forms of conflict patterns that occur are included in the type of interpersonal conflict which is a conflict between a group within the same organization, on the other hand the form of this conflict pattern includes latent and manifest conflicts because seen from the triggers of the conflict already visible or open, and has been known to many parties . 3.) Conflict resolution taken by the two parties uses a negotiation method with rescheduling for the purposes of the City of Surabaya